The Circulation and Politics of Knowledge: Climate Change and Livelihood Struggles in a Coastal Fishing Community - Sunil D. Santha (Glocalism: Journal of Culture, Politics and Innovation)
Exploring the role of knowledge circulation in everyday life could provide interesting insights on how different forms of knowledge shapes the lifeworld and subjective realities of people. In the context of everyday livelihood struggles of a coastal fishing community, this paper examines the nature of knowledge circulation at the local level and its micropolitics in wider social arenas. Exploring the nature of local knowledge systems prevalent among small-scale fishworkers, this paper further examines the politics of knowledge, when it circulates from the local social worlds to their solidarity networks. This paper is based on a qualitative study conducted in a coastal fishing village at Munambam situated along the Cochin Estuary in Kerala, India. The study was conducted in two phases. In the first phase of the study, data was collected through in-depth interviews by using a semi-structured interview schedule. In the second phase, a content analysis of media reports was carried out with an aim to analyse the discourses prevalent among diverse solidarity networks of fishworkers. The findings of this paper show that local knowledge is situated and intersectional. Further, the everyday lives of fishworkers are shaped by different knowledge claims that also signify their everyday struggles to access basic livelihood resources. It is amidst these diverse knowledge claims that one needs to critically examine the narratives of modernisation, climate change and the role of solidarity networks among fishworkers.